Unripe Papaya (Carica papaya L.) Seed Hexane Fraction Extract Inhibits Male Mice (Mus musculus) Spermatogenesis Stronger Than Unripe Papaya Seed Methanolic Extract - Satriyasa, Bagus Komang (BALI MEDICAL JOURNAL, 2016)
Background: Men and women have the same rights and obligations in family planning program.  Practically, participation in family planning program is still predominated by women while  participation of men is still low. Low participation of men in family planning program is due to very  limited choices in male contraceptive method. In recent years, studies have been refocused on  investigating traditional plants as antifertility herbal medicine for men. Studies on antifertility effects  of unripe papaya seeds have been done. However, similar studies on hexane fraction extract have not  yet been done. In this study, unripe seeds were collected from local Balinese papaya ( Carica papaya )  fruits.  Objective: This study was aimed to assess the effect of unripe papaya seeds hexane fraction  extract on spermatogenesis and the testosterone level of male mice. Hexane fraction extract of unripe  papaya seeds contains glycosides and triterpenoids, which is assumed to have an antifertility property,  so it can be used as a male contraceptive, although the mechanism of action remains to be elucidated.  Method: This study used pre-test and post-test control group design, using 30 male mice of balb C  strain, 12 weeks of age, weighing 20-22 gram, which were randomly grouped into 3 groups, each  consisting of 10 male mice. One control group (P0 = control group) was given double-distilled water,  and two treatment groups were given hexane fraction extract of unripe Carica papaya seeds 20  mg/20gram/day, and methanolic extract of unripe Carica papaya seeds 20 mg/20 gram/day (P1 and  P2, respectively). After 36 days of treatment, evaluation of the testes and blood of the male mice was  conducted. Results: Data were analysed by normality test of Kolmogorov-Smirnov Goodness of Fit,  homogeneity test, and Anova test. This study showed that spermatogonia A, primary pachytene  spermatocytes, spermatid and Sertoli cells were decreased significantly (p < 0,05) but Leydig cells  and testosterone levels were not decreased significantly (p > 0,05). Conclusion: It can be concluded  that hexane fraction extract of unripe Carica papaya seeds can decrease the mean number of  spermatogonia A cells, spermatocyte of primary pachytene spermatocytes, spermatid and Sertoli cells  better than methanolic extract of unripe Carica papaya seeds.
Keywords: Spermatogenesis, testosterone, Carica papaya, methanolic, extract.